Increased Fat-Free Body Mass and No Adverse Effects on Blood Lipid Concentrations 4 Weeks after Additional Meat Consumption in Comparison with an Exclusion of Meat in the Diet of Young Healthy Women - Klaus J. Petzke; Susen Lemke; Susanne Klaus (Journal of Nutrition and Metabolism)
Aims. To investigate whether changes of meat consumption can affect body composition and laboratory parameters in healthy, normal weight, young women without the aim to reduce body weight. Research Design and Methods. Women volunteered to eat low-fat meat in addition to their habitual diet (M) or to exclude meat products from their diet (NOM). After 4 weeks M and NOM were crossed over between subjects. Changes in nutrient intake, morphometrics and plasma parameters were compared during M and NOM. Results. Daily protein intake (means ± SD) was 2.25 ± 0.35 (25.2% of energy) and 1.15 ± 0.26 g/kg (14.0% of energy) during M and NOM, respectively. Fat-free body mass (FFM) increased during M (0.7±1.0 kg, P=.02) and decreased during NOM (-0.8±0.8 kg, P=.003). Body fat mass was unchanged. Concentrations of total cholesterol (-7%), LDL-cholesterol (-8%), and glucose (-4%) deceased significantly after M. Fasting glutamine concentrations were decreased by M and increased by NOM. Conclusions. Additional meat intake can increase FFM without adverse effects on blood lipid concentrations. Long-term studies are required. Urinary excretion of 3-methylhistidine could represent a biomarker for meat protein consumption.